Social Anomie and Drug Addiction (Drug Control Headquarters, Research and Education Office, 2004)
The present article addresses the relationshop between social anomie and drug addiction and tries to show that how we can apply anomie theory to clarify the aspects of this social problem in our society. By reviewing Durkheim's and Merton's anomie theories and Agnew's mental-social theory، this article attempts to show that despite of fundamental differences in these two theories، Iranian Society has an anomic situation and this situation has a high poteniality for tendency toward drug addiction/abuse.